Associations between cerebrospinal fluid markers of neuroinflammation and longitudinal measurements of white matter lesions. (31st December 2021) - Gertje, Eske Christiane; Janelidze, Shorena; van Westen, Danielle; Cullen, Nicholas; Palmqvist, Sebastian; Hansson, Oskar; Mattsson‐Carlgren, Niklas
Abstract: Background: The interplay between neuroinflammation and small vessel disease in the early stages of neurodegenerative disease is unclear. Here, we tested the association between cerebrospinal fluid (CSF) levels of biomarkers reflecting inflammatory processes and white matter lesion (WML) volume over time. Method: We included 582 cognitively unimpaired (CU) elderly and 279 patients with mild cognitive impairment (MCI). CSF samples were analyzed for interleukin (IL)–6, IL‐7, IL‐8, IL‐15, IL‐16, interferon‐gamma induced protein‐10 (IP‐10), monocyte chemoattractant protein 1 (MCP‐1), intercellular adhesion molecule 1(ICAM‐1), vascular adhesion molecule 1 (VCAM‐1), placental growth factor (PlGF), and fms‐related tyrosine kinase 1 (sFlt‐1) as well as vascular endothelial growth factor (VEGF). WML volumes were measured at baseline, and at 2, 4 and 6 years. Analyses were adjusted for Aβ status, age and gender. Result: In CU, lower levels of PlGF (β=‐0.02, p=0.027) were associated with increasing WML burden over time. However, in MCI lower levels of PlGF (β=‐0.05, p<0.001), IL‐16 (β=‐0.04, p=0.010), VEGF (β=‐0.03, p=0.012), IL‐6 (β=‐0.04, p=0.005), IL‐8 (β=‐0.03, p=0.016) and MCP‐1 (β=‐0.03, p=0.012), as well as higher levels of sFlt‐1 (β=‐0.03, p=0.034) were associated with longitudinal increase in WML. Conclusion: CSF markers mediating angiogenesis, such as PlGF and VEGF, are associated with longitudinal WML volume changes, especially in individuals with MCI.